Analisis Kesalahan Siswa Pada Materi Pertidaksamaan Linear Satu Variabel Yang Memuat Nilai Mutlak - Jihan Hidayah Putri; Suci Rahmadani; Sri Mariani; Minta Ito Simamora (Departement of Mathematics Education, 2023)
Many students in class X at Al-Wasliyah 12 Perbaungan continue to struggle with the concept of solving linear inequalities with one variable that contains an mutlake value, according to data collected at the school. In order to help students avoid making the same mistakes, it is helpful to understand how they err when attempting to solve linear inequalities with one mutlake value in one variable. The teacher needs to understand whether or not the students' errors stem from a lack of understanding of the material being taught, as well as the types of questions on which the majority of errors occur. So the author's goal is to analyze common issues when teaching students to solve one-variable linear inequalities with mutlake values so that students can more easily solve such problems in the future. This study employed a qualitative, descriptive research strategy. Tests and interviews were used as data collection techniques. The reliability and accuracy of the measuring device used were first establishedit organizes.